Răspuns :
[tex]1)\left\{\begin{matrix}
2x - 3y = 8\\
3x + y = 1\end{matrix}\right.[/tex]
[tex]3x + y = 1[/tex]
[tex]y = 1 - 3x[/tex]
[tex]2x - 3y = 8[/tex]
[tex]2x - 3(1 - 3x) = 8[/tex]
[tex]2x - 3 + 9x = 8[/tex]
[tex]2x + 9x = 8 + 3[/tex]
[tex]11x = 11 \: | \div 11[/tex]
[tex]x = 1[/tex]
[tex]y = 1 - 3x[/tex]
[tex]y = 1 - 3 \times 1[/tex]
[tex]y = 1 - 3[/tex]
[tex]y = - 2[/tex]
[tex]2)\left\{\begin{matrix}
3x + 2y = - 7 \: | \times 3\\
4x + 3y = - 10 \: | \times ( - 2)\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
9x + 6y = - 21\\
- 8x - 6y = 20\end{matrix}\right.[/tex]
[tex]9x - 8x + 6y - 6y = - 21 + 20[/tex]
[tex]x = - 1[/tex]
[tex]9x + 6y = - 21[/tex]
[tex]9 \times ( - 1) + 6y = - 21[/tex]
[tex] - 9 + 6y = - 21[/tex]
[tex]6y = - 21 + 9[/tex]
[tex]6y = - 12 \: | \div 6[/tex]
[tex]y = - 2[/tex]
2x - 3y = 8\\
3x + y = 1\end{matrix}\right.[/tex]
[tex]3x + y = 1[/tex]
[tex]y = 1 - 3x[/tex]
[tex]2x - 3y = 8[/tex]
[tex]2x - 3(1 - 3x) = 8[/tex]
[tex]2x - 3 + 9x = 8[/tex]
[tex]2x + 9x = 8 + 3[/tex]
[tex]11x = 11 \: | \div 11[/tex]
[tex]x = 1[/tex]
[tex]y = 1 - 3x[/tex]
[tex]y = 1 - 3 \times 1[/tex]
[tex]y = 1 - 3[/tex]
[tex]y = - 2[/tex]
[tex]2)\left\{\begin{matrix}
3x + 2y = - 7 \: | \times 3\\
4x + 3y = - 10 \: | \times ( - 2)\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
9x + 6y = - 21\\
- 8x - 6y = 20\end{matrix}\right.[/tex]
[tex]9x - 8x + 6y - 6y = - 21 + 20[/tex]
[tex]x = - 1[/tex]
[tex]9x + 6y = - 21[/tex]
[tex]9 \times ( - 1) + 6y = - 21[/tex]
[tex] - 9 + 6y = - 21[/tex]
[tex]6y = - 21 + 9[/tex]
[tex]6y = - 12 \: | \div 6[/tex]
[tex]y = - 2[/tex]